2015
DOI: 10.1371/journal.pgen.1005217
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Transcriptional Coactivator Sub1 Leads to Genome-Wide Re-distribution of Clustered Mutations Induced by APOBEC in Active Yeast Genes

Abstract: Mutations in genomes of species are frequently distributed non-randomly, resulting in mutation clusters, including recently discovered kataegis in tumors. DNA editing deaminases play the prominent role in the etiology of these mutations. To gain insight into the enigmatic mechanisms of localized hypermutagenesis that lead to cluster formation, we analyzed the mutational single nucleotide variations (SNV) data obtained by whole-genome sequencing of drug-resistant mutants induced in yeast diploids by AID/APOBEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 83 publications
(93 reference statements)
6
61
1
Order By: Relevance
“…It is possible that a larger mutational harvest would reveal a significant transcription strand bias, especially in highly transcribed genes, but in our data, any such bias was overwhelmed by the observed replication strand bias. In contrast, Lada et al found that most mutations caused by the lamprey cytosine deaminase, PmCDA1, in nondividing yeast were correlated with transcription (40). Together, these observations suggest that in dividing cells, the greatest source of C:G to T:A mutations is the deamination of cytosines in the template for the lagging strand synthesis, but transcription may play a larger role in nondividing cells.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that a larger mutational harvest would reveal a significant transcription strand bias, especially in highly transcribed genes, but in our data, any such bias was overwhelmed by the observed replication strand bias. In contrast, Lada et al found that most mutations caused by the lamprey cytosine deaminase, PmCDA1, in nondividing yeast were correlated with transcription (40). Together, these observations suggest that in dividing cells, the greatest source of C:G to T:A mutations is the deamination of cytosines in the template for the lagging strand synthesis, but transcription may play a larger role in nondividing cells.…”
mentioning
confidence: 95%
“…One characteristic of cancer genome mutations is that they are found in clusters, suggesting that they occur in genomic regions that contain stretches of ssDNA (34). Although a number of cellular processes, including replication, transcription, and recombination, have been proposed as sources of ssDNA targets for APOBEC3s (13,34,(40)(41)(42), experimental evidence for these ideas is limited. The data presented here suggest that the LGST at the replication forks of rapidly dividing cancer cells would be accessible to these enzymes, and hence the cytosines mutated in cancer genomes should be found preferentially in the LGST compared with the LDST.…”
mentioning
confidence: 99%
“…Cytidine deamination by AID on ssDNA during transcription of variable regions in the immunoglobulin locus is required for the initiation of both class-switch recombination and somatic hypermutation [18,19]. Interestingly, the activity of AID is regulated at the transcription bubble through the interaction with transcriptional co factors that assist with AID catalytic activity [20,21]. The expression of AID in B cells is essential as AID deficiency leads to Hyper-IgM syndrome and the inability to produce antibodies other than IgM M2 [22].…”
Section: Evolution Of Apobec3 Activitymentioning
confidence: 99%
“…For a related family member AID, which normally deaminates the immunoglobulin genes to enable antibody maturation and class switching [11], targeting of AID to the correct genomic region and maximizing its access to both strands of the genomic DNA requires many interacting partner [186]. Although AID can access other regions of the genome, it is thought that interactions with transcription machinery occur to facilitate its specific role in deaminating cytosine in immunoglobulin genes [20,21]. These protein-protein interactions may not only assist in targeting immunoglobulin genes during B-cell activation, but may be required for AID to catalyze deaminations since its catalytic rate is slow [187].…”
Section: Role Of Apobec In Somatic Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation